"My BMI is too high for Plan B." A changing population of women seeking ulipristal acetate emergency contraception online. Issue 3 (15th March 2020) - Cleland, Kelly; Wagner, Brandon; Smith, Nicole K.; Trussell, James
ABSTRACT: Emergency contraceptive (EC) pills may be less effective for women with higher body mass index (BMI), but little is known about public response to the fact that EC may lose efficacy as weight increases. In November 2013, European authorities changed the label for a levonorgestrel EC product to warn of a reduction in effectiveness for women with higher BMI, garnering significant media coverage in the United States. Ulipristal acetate (UPA) EC may be more effective than levonorgestrel for women with BMI levels designated as obese. Among 8, 019 women who received UPA from the online pharmacy KwikMed from 2011 to 2015 and self-reported their height, weight and reasons for seeking UPA online, we analyzed changes in the proportion of women in different BMI categories before and after the label change. For the 25 month-period after the label change, the proportion of women in the obese category rose by 26.7 percentage points relative to the 35 months before (B = 0.2665, p < .01). Mean BMI (25.5 versus 29.4, p < .001) and average weight (148.6 pounds versus 175.5 pounds, p < .001) of users were higher after the label change. Some women appear to have acted on the information that EC efficacy may be associated with body weight.